Legal Implications of the Establishment of Alternative Institution of Dispute Resolution of Indonesian Banking (LAPSPI) on Sharia Banking Dispute Settlement in Indonesia - nun harrieti (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
Sharia banking is specifically regulated by Law No. 21 on 2008 of Sharia Banking, the provision of Article 55 of the law provides that the resolution of sharia banking disputes shall be conducted by the courts within the scope of religious courts, but does not rule out the existence of other forum authority as agreed by the parties. At the end of 2015, an Alternative Institution of Dispute Resolution of Indonesian Banking (LAPSPI) has been established and registered as a follow-up to the Financial Services Authority Regulation no. 1 / POJK, 07/2014 About the Alternative Dispute Resolution Institution in the Financial Services Sector. It is interesting to be reviewed what the legal implication of LAPSPI's establishment on dispute resolution of sharia banking in Indonesia is. This research was conducted by applying normative juridical approach method with analytical description research specification. Legal implications of LAPSI's establishment are requiring sharia banks to make LAPSPI as the only space and organization recognized in sharia banking external dispute resolution based on LAPSPI article of the association. Keywords: Dispute Settlement, LAPSPI, Sharia Banking.